2021
DOI: 10.6007/ijarped/v10-i1/8547
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Mastery Level of Arabic Academic Vocabulary (AAV): A Study Among Malaysian Public Universities

Abstract: This quantitative study aims to identify the mastery level of Arabic academic vocabulary (AAV) as well as to identify differences in AAV mastery among students between six public universities in Malaysia using receptive and productive AAV test instruments. Researchers constructed AAV test questions based on the test format introduced by Schmitt (2000) with some modifications. A total number of 50 academic vocabularies were filtered from the Academic Word List (AWL) proposed by Davies and Gardner (2013) and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Another study found vocabulary learning strategies to equip students to continue to higher education (Baharudin & Ismail, 2014). There were studies on the analysis of Arabic vocabulary skills (Samsun Baharun et al, 2021); (Rabiatul Aribah et al, 2014). A study on the correlation of Arabic language skills with Hifzil Quran found that students with maharah al-lughah had higher Quran memorization abilities (Fauziah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another study found vocabulary learning strategies to equip students to continue to higher education (Baharudin & Ismail, 2014). There were studies on the analysis of Arabic vocabulary skills (Samsun Baharun et al, 2021); (Rabiatul Aribah et al, 2014). A study on the correlation of Arabic language skills with Hifzil Quran found that students with maharah al-lughah had higher Quran memorization abilities (Fauziah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ni'mah (2017) found that there was a positive correlation between vocabulary mastery and students' speaking ability. Baharun and friends also reinforced that vocabulary affects all mastery of language competencies such as the ability to hear, speak, read and write (Samsun Baharun et al, 2021). Some studies above have explained the importance of vocabulary knowledge to support the mastery of language skills.…”
Section: Introductionmentioning
confidence: 93%